Endophytic Nanotechnology: An Approach to Study Scope and Potential Applications - Meena, Mukesh; Zehra, Andleeb; Swapnil, Prashant; Harish,; Marwal, Avinash; Yadav, Garima; Sonigra, Priyankaraj (Frontiers in Chemistry, 2021)
Nowadays, nanotechnology is a very advanced and popular technology with huge potentials. Nanotechnology has been very well explored in the field of electronics, automobiles, construction, medicine, and cosmetics but the most important exploration of this technology is yet to be needed in the field of agriculture also. Due to climate change, each year around 40% of crops are facing abiotic and biotic stress, therefore the global demand for food production increasing and nanotechnology is the best method to mitigate challenges in disease management in crops by reducing the use of chemical inputs such as herbicides, pesticides, and fungicides. The use of these toxic chemicals is potentially harmful to humans and the environment. Therefore, the use of NPs reduces the problems in plant disease management as fungicides/ bactericides or as nanofertilizers due to having a small size, more surface area with high reactivity. There are several methods that have been used to synthesize NPs such as physical and chemical methods. Specially, we need ecofriendly and nontoxic methods, for the synthesis of NPs. Some biological organisms like plants, algae, yeast, bacteria, actinomycetes and fungi have been emerged as the superlative candidate for the biological synthesis of NPs also considered as green synthesis. Among these biological methods, endophytic microorganisms have been widely used to synthesize NPs with low metallic ions which opens a new possibility on the edge of biological nanotechnology. In this review, we will have discussed the different methods of synthesis of NPs such as top-down, bottom-up and green synthesis (specially including endophytic microorganisms) based methods and their mechanisms, different forms of NPs such as magnesium oxide nanoparticles (MgO-NPs), copper nanoparticles (Cu-NPs), chitosan nanoparticles (CS-NPs), β-d-glucan nanoparticles (GNPs), engineered nanoparticles (quantum dots, metalloids, nonmetals, carbon nanomaterials, dendrimers, and liposomes) and their molecular approaches in various aspects. At the molecular level, nanoparticles can also be used as molecular tools to carry genetic material during genetic engineering of plants such as mesoporous silica nanoparticles (MSN) and RNA-interference molecules. In plant disease management, NPs can be used as biosensors to diagnose the disease.